2021
DOI: 10.3389/fsufs.2021.646980
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-Loaded Polymeric Micelles Inhibit Enteric Bacterial Pathogens on Spinach Leaf Surfaces During Multiple Simulated Pathogen Contamination Events

Abstract: Protecting fresh-packed produce microbiological safety against pre- and post-harvest microbial pathogen contamination requires innovative antimicrobial strategies. Although largely ignored in the scientific literature, there exists the potential for gross failure in food safety protection of fresh fruits and vegetables leading to opportunity for multiple produce contamination events to occur during production and post-harvest handling of food crops. The primary objective of this research was to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…GNP treatment achieved the greatest numerical reductions in the numbers of both organisms, though survivor numbers did not statistically differ from those obtained from HOCl samples (Figure 2). The reductions observed in the current study for GNP treatment were significantly less than those we recently reported on spinach [20]. A lack of more impressive reductions in microbial counts may be at least partially explained by the second inoculation/contamination event, where the numbers of the organisms were refreshed on sample surfaces.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…GNP treatment achieved the greatest numerical reductions in the numbers of both organisms, though survivor numbers did not statistically differ from those obtained from HOCl samples (Figure 2). The reductions observed in the current study for GNP treatment were significantly less than those we recently reported on spinach [20]. A lack of more impressive reductions in microbial counts may be at least partially explained by the second inoculation/contamination event, where the numbers of the organisms were refreshed on sample surfaces.…”
Section: Discussioncontrasting
confidence: 90%
“…Additionally, our group reported geraniol-loaded nanoparticles outperformed unencapsulated geraniol and 200 mg/L HOCl on spinach surfaces, reducing E. coli O157:H7 and S. Typhimurium to non-detectable numbers (<0.5 log 10 CFU/cm 2 ) when applied multiple days prior to pathogen application. Similar effects were observed when E. coli O157:H7or S. Typhimurium-inoculated spinach was sanitizer-treated and then re-inoculated 3 days later, simulating pathogen contamination of the food crop during pre-and post-harvest operations [20]. These findings data indicated encapsulated geraniol afforded longer-lasting food safety protection versus other conventional chemical sanitizing treatments, even under conditions of gross failures in good agricultural practices (GAPs).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Tomato samples were inoculated by spot-inoculation of cocktailed E. coli O157:H7 and S. typhimurium cells using the same method previously reported [9,10]. Briefly, 0.1 mL total inoculum fluid was applied by evenly distributing ten 10.0 µL spots over the three combined tomato discs within a sample.…”
Section: Tomato Sample Inoculation By Cocktailed Pathogensmentioning
confidence: 99%